Relationship of LST, NDVI, and NDBI using Landsat-8 data in Duhok city in 2019-2022 (Journal of Planner and Development, 2023)
One of the most significant elements influencing weather, climate, and the environment is vegetation cover. Normalized Difference Vegetation Index (NDVI) and Normalized Difference Built-up Index (NDBI) over the years 2019–2022 were estimated based on four Landsat 8 TIRS’s images covering Duhok City. Using the radiative transfer model, the city's land surface temperature (LST) during the next four years was calculated. The aim of this study is to compute the temperature at the land's surface (LST) from the years 2019-2022 and understand the link, between LST, NDVI, and NDBI and the capability for mapping by LANDSAT-8 TIRS's. The findings revealed that the NDBI and the NDVI had the strongest correlation with the value R 2 = 82 in the year 2022. In comparison to the Normalized Difference vegetation index(NDVI), there was a relatively larger correlation between the NDBI and the surface temperature. However, the Normalized Difference Building up Index (NDBI) and temperature were determined to have the smallest correlation.